Corporate Sustainability and Trade Credit: Evidence from ESG - Wang Shiyu (SHS Web of Conferences, 2023)
ESG is an extension of the concept of green investment and reflects the concept of sustainable development of enterprises. More and more enterprises are using trade credit financing for their business which is an important part of debt financing. But the influence of corporate ESG performance on trade credit financing has not been explored entirely. We investigate whether and how ESG rating affect the amount of trade credit financing, using a sample of more than 3000 Chinese listed firms from 2011 to 2020. The results show that enterprises with good ESG performance can obtain more trade credit financing. In addition, the results remain significant after a series of robustness tests. The above conclusions not only enrich the research on the economic consequences of corporate ESG performance, but also provide empirical evidence for enterprises to effectively improve trade credit financing.